2020
DOI: 10.1016/j.ekir.2020.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B and T Cells and Their Association With Clinical Response in New-Onset Lupus Nephritis Patients

Abstract: Single-versus multiple-sample method to measure glomerular filtration rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Following immunosuppression in responders, Breg populations increased. In contrast, no noticeable change was seen in non-responders [19] .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Following immunosuppression in responders, Breg populations increased. In contrast, no noticeable change was seen in non-responders [19] .…”
Section: Discussionmentioning
confidence: 70%
“…The proportion of Bregs in LN patients and daily steroid dose were found to be negatively correlated by Heinemann et al [1] . Also recently Girimaji et al [19] reported that after six months of immunosuppression initiation, Bregs in LN patients become comparable to HC with no significant difference between them. This finding was observed in all cases irrespective of the type of immunosuppression received by the studied cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients with lupus nephritis had a significantly decreased in circulating IL-10+ Bregs levels compared to health controls ( 51 ). Patients with new-onset lupus nephritis had a decrease in CD19+CD5+CD1d high IL-10+ Bregs and restored Breg deficiency in patients who respond to immunosuppressive medications ( 48 ). The percentage of peripheral CD19+CD24 high CD27+ B cells with IL-10 and IL-35 production was low in patients with new-onset SLE ( 47 , 52 ).…”
Section: Imbalance Of Immune Regulatory Cells In Slementioning
confidence: 99%